Development and research of methods of substantiation of efficiency of using acoustic screens for noise suppression in the airport working zone - Токарев, В. И.; Шило, В. Ф. (Proceedings of National Aviation University (archive), 2000)
Presented are the results of models and algorithm estimation of screen use in the open field. The model takes into account the screen geometric parameter, the effects of sound waves reflection from underlying surface, absorption of acoustic oscilations by atmosphere and by protection green felts. Presented are also the results of investigation of air temperature and wind speed influence on the efficiency of acoustic screen use